Iran's nuclear programme and diplomacy under pressure. Issue 5 (27th May 2020) - Unknown
Abstract : A recent explosion at the Natanz nuclear complex set back Iran's nuclear development by one to two years but may encourage Iran to move its centrifuge production underground, where it will be hidden from international supervision. While Iran is also under diplomatic pressure, the Joint Comprehensive Plan of Action (JCPOA) of 2015 is likely to survive until the US presidential election in November.